Disturbance of sensory filtering in dementia with Lewy bodies: comparison with Parkinson's disease dementia and Alzheimer's disease. Issue 1 (16th December 2004) - Perriol, M-P; Dujardin, K; Derambure, P; Marcq, A; Bourriez, J-L; Laureau, E; Pasquier, F; Defebvre, L; Destée, A
Abstract : Introduction: Prepulse inhibition (PPI) is considered to mirror an organism's ability to filter out irrelevant sensory or cognitive information. The disruption of PPI has never been studied in individuals suffering from dementia with Lewy bodies (DLB). As attention deficits largely contribute to cognitive impairment in DLB, an investigation with a PPI paradigm is useful for differential diagnosis of DLB versus Alzheimer's disease (AD) and Parkinson's disease dementia (PDD). Objective and methods: PPI of the N1/P2 component of auditory evoked potentials was used to investigate the early stages of attention selectivity in 10 DLB, 10 AD, and 10 PDD patients, as well as in 10 healthy controls. The PPI paradigm consisted of the presentation of sound pulses (40 ms, 115 dB) preceded by a prepulse (40 ms, 80 dB). Sound stimuli were presented in a total of 80 trials in a pseudo-random order. Results: Non-parametric analyses of variance revealed a significant group effect on the 120 ms lead interval. Retrospective analyses revealed that PPI was significantly reduced in DLB compared to healthy controls and AD. In the PDD group, the disturbance was of intermediate intensity. Conclusion: The present study revealed a severe disturbance of PPI in DLB patients. The DLB patients displayed a specific disruption profile in terms of magnitude as well as time course.